1988
DOI: 10.1128/aac.32.5.689
|View full text |Cite
|
Sign up to set email alerts
|

Aminoglycoside resistance among Pseudomonas aeruginosa isolates with an unusual disk diffusion antibiogram

Abstract: In recent years, a number of clinical microbiology laboratories have isolated Pseudomonas aeruginosa with the unusual aminoglycoside disk diffusion result of resistance to both amikacin and gentamicin but susceptibility to tobramycin (AFGrTS). A total of 39 isolates of P. aeruginosa reported to have this resistance pattern were retested by the standard National Committee for Clinical Laboratory Standards disk diffusion procedure; 30 strains (77%) were confirmed to be ArGFTS. These 30 isolates were further exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0

Year Published

1990
1990
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 12 publications
3
6
0
Order By: Relevance
“…According to the current study, methicillin resistant CoNS were 77.3% which is in line with the study that reported 72.5% resistant strains [37]. The present study also showed a single isolate of CoNS resistant to vancomycin which is less from the isolates found India [37]. The emergence of vancomycin resistance in CoNS in our teaching hospital may pose therapeutic problems, and therefore the empirical antibiotic treatment of suspected infections caused by CoNS should be prescribed according to antimicrobial susceptibility testing.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…According to the current study, methicillin resistant CoNS were 77.3% which is in line with the study that reported 72.5% resistant strains [37]. The present study also showed a single isolate of CoNS resistant to vancomycin which is less from the isolates found India [37]. The emergence of vancomycin resistance in CoNS in our teaching hospital may pose therapeutic problems, and therefore the empirical antibiotic treatment of suspected infections caused by CoNS should be prescribed according to antimicrobial susceptibility testing.…”
Section: Discussionsupporting
confidence: 90%
“…Methicillin resistant CoNS have become the predominant pathogen and increasing dramatically in hospitalized patients [35,36]. According to the current study, methicillin resistant CoNS were 77.3% which is in line with the study that reported 72.5% resistant strains [37]. The present study also showed a single isolate of CoNS resistant to vancomycin which is less from the isolates found India [37].…”
Section: Discussionsupporting
confidence: 89%
“…These isolates were recovered from different patients at The Mount Sinai Hospital in New York, NY (four isolates), from the Saint Joseph Hospital in Omaha, Nebraska (five isolates), and from the Veterans Administration Medical Center in Omaha (one isolate). All strains were identified as P. aeruginosa by previously described methods [5][6][7] and showed the ArGrT s antibiogram when tested by the NCCLS disk diffusion procedure [25]. Multiple passaging was avoided to prevent possible loss of antibiotic resistance.…”
Section: Methodsmentioning
confidence: 99%
“…Agar dilution was performed by the NCCLS standard method [26] as described earlier [5]. Test strains were spot inoculated onto Mueller-Hinton agar (MHA) (BBL, Cockeysville, Md) with a multipoint inoculator.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation